Bunka Gaikō (Japan’s Cultural Diplomacy) :|re-constructing Japanese identity in France and Turkey (1952-1989) - Karaoğlu, Semiha. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Japan has evolved into a cultural nation in the aftermath of World War II owing to the promulgation of the Article 9 of the Constitution of Japan. Given its pacifist culture and emerging role as a responsible member of the global society, cultural diplomacy became the primary and immediate foreign policy instrument to reconstruct Japanese identity in international relations long before the theory of Soft Power emerged. The present research unveils Japan’s identity reconstruction through cultural diplomacy as a rehabilitative and constructive foreign policy mechanism to heal its image as a peace-loving nation by comparing Japan’s cultural diplomacy in France and Turkey between 1952 and 1989 comparatively to discern what kind of perception of Japan has emerged as a product of Japan’s international cultural policies in both countries. Ultimately, the thesis reveals that Japan’s cultural diplomacy in France has generated an intellectual ecosystem, whereas, in Turkey, the perception of Japan and Japanese culture remains underdeveloped due to the lack of an official culture house—inaugurated by the Government of Japan—which can constitute a legitimate institute or culture house to coordinate international cultural policies.
Keywords: Cultural diplomacy -- Japan -- History.; Japan -- Foreign relations -- Turkey.; Japan -- Foreign relations -- France.